Mortality Risk Reduction Benefit Measurement By Overlapping Generations Model - Hisa Morisugi; Naoki Sakamoto (European Regional Science Association (ERSA), 2013)
This study proposes a consistent definition of mortality risk reduction benefit in accordance with general definition of benefit, willingness to pay, more concretely, consumption or Equivalent Variation, of any policy and projects such as tax reforms, transportations, environments, infrastructures, natural disaster preventions, etc. In order to formulate mortality risk reduction benefit this study describes the economy by the overlapping generation growth model with perpetual youth where the mortality risk is described by the Poisson process with a constant mortality probability per unit of time. The annual welfare gain of mortality risk reduction is defined as the change in the expected utility level in the steady state induced by the change in mortality probability and resulting consumption level. Then the annual benefit of mortality risk reduction is defined by applying the concept of Equivalent Variation to the expected utility as the amount of annual consumption increase in the steady state for before the mortality risk reduction such that the resulting expected utility level equals that for the case after the mortality risk reduction. The steady state consumption and capital stock level is determined by two simultaneous equations, Euler equation and market clearance given the mortality risk level. The mortality risk does not change the consumption directly, but does change it indirectly through the change in capital stock, which is different from the static analysis. The static definition does not arrow for the increase in consumption level. Therefore it is underestimation. This is because the static definition does not recognize that capital stock is not an exogenous but an endogenous variable. Finally this study measures the impacts of mortality increase due to the heat sick and the natural disaster increase derived by global warming at 2113 in Japan. . Keywords: mortality risk reduction benefit, overlapping generation growth model, cost benefit analysis.
Keywords: H43; 330